Evaluasi Perhitungan, Penyetoran, dan Pelaporan Pajak Penghasilan Pasal 23 pada CV XYZ - Vincensia Rena Dirapuspita; Dwi Suhartini (Akuntansi, 2024)
Article 23 mandates a tax on capital gains, service awards, prizes, and other forms of income (excluding those already deducted under Article 21). Both the payer and recipient are obligated to withhold and remit this tax to the relevant authorities. This study aims to evaluate CV XYZ's compliance with the Income Tax Law in terms of calculating, depositing, and reporting Article 23 income tax. Employing a descriptive qualitative methodology, our findings indicate that CV XYZ adheres to Income Tax Law No. 36 of 2008. Taxpayers are often required to submit a tax return (SPT) for the Income Tax Period, detailing all transactions, tax calculations, and payments. Adherence to these reporting standards promotes legal compliance, consistent revenue, and effective public fund management. Accurate understanding and implementation of Article 23 are crucial for fostering public trust in the tax system. This enhances system efficiency, enabling the government to optimize tax management while taxpayers contribute to sustainable and inclusive economic growth in Indonesia.